2020
DOI: 10.1016/j.biomaterials.2020.120355
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, a multi-functional glycoprotein: Active therapeutic, drug nanocarrier & targeting ligand

Abstract: Recent progress in protein-based nanomedicine, inspired by the success of Abraxane® albumin-paclitaxel nanoparticles, have resulted in novel therapeutics used for treatment of challenging diseases like cancer and viral infections. However, absence of specific drug targeting, poor pharmacokinetics, premature drug release, and off-target toxicity are still formidable challenges in the clinic. Therefore, alternative protein-based nanomedicines were developed to overcome those challenges. In this regard, lactoferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 223 publications
(318 reference statements)
0
107
0
Order By: Relevance
“…Increasing numbers of studies indirectly suggest that the Lf-mediated neuroprotection against neurodegenerative disorders is attributed to its biological characteristics. (1) In inflamed tissues, the content of Lf is significantly increased [60], and Lf can reduce the expression of the pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 to exert its anti-inflammatory effects [61]; (2) Lf can significantly increase the content of superoxide dismutase (SOD) and reduce the generation of ROS by inhibiting the Fenton reaction [16], thereby exerting ROS modulator effects; (3) Lf can regulate the expression of proteins involved in lipid degradation by controlling the activity of the cAMP/extracellular regulatory protein kinase (ERK) signaling pathway via LRP1 [28], thereby regulating lipid metabolism; (4) increased LfR expression in the brains of patients with neurodegenerative diseases suggests that Lf may play a significant role in the pathogenesis and prevention of neurodegenerative diseases [62]; (5) Lf acts as a normoxic mimetic of hypoxia that is capable of stabilizing hypoxia-inducible factor 1α (HIF-1α) [63] (6); Lf elevates the mRNA and protein levels of brain-derived neurotrophic factor (BDNF) and components of its signaling pathway [64].…”
Section: The Important Role Of Lf In the Onset And Prevention Of Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing numbers of studies indirectly suggest that the Lf-mediated neuroprotection against neurodegenerative disorders is attributed to its biological characteristics. (1) In inflamed tissues, the content of Lf is significantly increased [60], and Lf can reduce the expression of the pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 to exert its anti-inflammatory effects [61]; (2) Lf can significantly increase the content of superoxide dismutase (SOD) and reduce the generation of ROS by inhibiting the Fenton reaction [16], thereby exerting ROS modulator effects; (3) Lf can regulate the expression of proteins involved in lipid degradation by controlling the activity of the cAMP/extracellular regulatory protein kinase (ERK) signaling pathway via LRP1 [28], thereby regulating lipid metabolism; (4) increased LfR expression in the brains of patients with neurodegenerative diseases suggests that Lf may play a significant role in the pathogenesis and prevention of neurodegenerative diseases [62]; (5) Lf acts as a normoxic mimetic of hypoxia that is capable of stabilizing hypoxia-inducible factor 1α (HIF-1α) [63] (6); Lf elevates the mRNA and protein levels of brain-derived neurotrophic factor (BDNF) and components of its signaling pathway [64].…”
Section: The Important Role Of Lf In the Onset And Prevention Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Lactoferrin (Lf) was first identified in bovine milk by Sorensen in 1939, and Lf was subsequently isolated from human milk in 1960 [ 1 , 2 ]. Lf is an iron-binding glycoprotein with a molecular weight of approximately 80 kDa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while antibodies are most commonly associated with antigen targeting, ADCs are also being developed to conjugate cytotoxic drugs to tumor-specific receptor ligands. While these targeting modalities are not covered in this review, we point readers to these recently published reviews [191][192][193][194][195].…”
Section: Novel Target Antigensmentioning
confidence: 99%
“…Due to its positive effects, it is commercially purified from milk and added as an active ingredient to infant milk formulas, food supplements, food products, beverages, cosmetics, and pet foods [ 1 , 2 , 3 ]. Several clinical studies showed its potential to be used as a primary or adjuvant agent in the treatment of infections, cancers, sepsis, and other diseases [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%